The Effect Of Variety On High Plants And Node Of Corn Forage - Didah Maidah; Nyimas Popi Indriani; Iin Susilawati (Unpad Press, 2022)
The purpose of this study was to know the effect of variety on high plants and node of corn forage by knowing which varieties of corn gave the highest yield to plant heigt and node of corn forage. This research was conducted from February – April 2022 located in experimental garden in Forage Crop Laboratory, Animal Husbandry Faculty, Universitas Padjadjaran. This study used experimental method with randomized block design (RBD). There were four treatments used P1 = Bonanza varieties, P2 = Janisa varieties, P3= Asian 86 varieties and P4 = Sweet Lady varieties with six replications. The observed variables included plant height and node of corn plants. The result of statistical showed that the treatment of various varieties of corn had significant effect on plant height, and produced the highest plant height varieties of Janisa which is 175,42 cm, varieties of Bonanza which is 172,18 cm and varieties of Asia which is 161,58 cm and showed had no significant (P>0.05) on node of corn plants.